Assessing the effectiveness of public participation in regional regulation formulation: Evidence from South Tangerang City, Indonesia - Pasaribu, Ahmad Jamil; Suradika, Agus; Mawar; Andriansyah, Andriansyah (Social Sciences Insights Journal, 2025)
This study aims to analyze the effectiveness of public participation in the formulation of regional regulations (Perda) in South Tangerang City and to examine how legal, institutional, and sociocultural factors shape the participatory process. It also seeks to determine whether existing legislative frameworks, particularly Law No. 13 of 2022 are implemented as intended in facilitating meaningful participation. The research employs an empirical legal approach supported by qualitative methods, combining normative analysis of legislation with field data obtained through in-depth interviews, participant observation, and document review. Data were analyzed using Miles and Huberman’s interactive model, while the effectiveness of participation was assessed through Soerjono Soekanto’s five legal effectiveness factors. The study finds that although the legal framework formally guarantees public participation, its implementation within the DPRD of South Tangerang City remains limited, inconsistent, and largely procedural. Participation tends to involve only invited stakeholders, many of whom lack adequate understanding of the substantive issues, resulting in low-quality input. Institutional gaps, particularly the absence of explicit participation procedures in the DPRD Standing Orders and limited access to draft regulations further weaken engagement. Sociocultural conditions indicate a shifting but still uneven participatory legal culture, where public involvement is recognized yet not fully realized in practice.